Insights Into Various Aspects of Oral Health 2017
DOI: 10.5772/intechopen.68446
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Nuclear and Oxidative DNA Damage

Abstract: Oral health is an important aspect of the overall health status of an individual. DNA damage has been associated with oral health and dental factors due to the increased of oxidative stress (OxS). DNA damage can produce a wide range of effects on human health. These effects could appear immediately, but others do not become evident much later. Chronic diseases have been study to understand their mechanisms, clinical implications, and the development of secondary disease such as cancer. Periodontitis is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Nuclear extensions and nuclear buds (NBUDs), which can generate MN, have a source similar to MN and are associated with the gene amplification process [23,26,[29][30][31]. Binucleated cells (BN) are caused by defects in cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear extensions and nuclear buds (NBUDs), which can generate MN, have a source similar to MN and are associated with the gene amplification process [23,26,[29][30][31]. Binucleated cells (BN) are caused by defects in cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Plentiful research studies have indicated a higher level of 8-OHdG in GCF and saliva of patients with periodontitis compared to healthy ones, as well as a significant association with periodontal clinical parameters [ 18 , 19 , 20 , 21 ]; in addition, levels are significantly reduced by periodontal treatment [ 19 , 22 ] but with no difference between local levels of 8-OHdG in people with gingivitis and periodontitis, as well as among patients with aggressive and chronic periodontitis [ 20 ]. Several studies have indicated that the level of 8-OHdG is directly related to the presence and/or amount of bacteria such as Porphyromonas gingivalis , Tannerella forsythia , Treponema denticola , and Streptococcus anginosus [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%